Pension Policies, Retirement and Human Capital Depreciation in Late Adulthood - Plamen Nikolov; Alan Adelman (Institute of Labor Economics (IZA), 2020)
Economists have mainly focused on human capital accumulation and considerably less on the causes and consequences of human capital depreciation in late adulthood. Studying human capital depreciation over the life cycle has powerful economic consequences for decision-making in old age. Using data from China, we examine how a new retirement program affects cognitive performance. We find large negative effects of pension benefits on cognitive functioning among the elderly. We detect the most substantial impact of the program on delayed recall, a significant predictor of the onset of dementia. We show suggestive evidence that the program leads to larger negative impacts among women. We demonstrate that retirement and access to a retirement pension plan plays a significant role in explaining cognitive decline at older ages.
Keywords: O12; J24; J26; H55; H75; O15; 330; life cycle; cognitive functioning; cognition; aging; health; mental retirement; middle-income countries; LMICs; developing countries; China